Gaya Komunikasi Desy Genoveva Di Akun Media Sosial Tiktok @Desygenoveva_ - Sefrina, Dhea Rizqi (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2024)
Competition for content creators on TikTok social media gives rise to creativity and uniqueness in creating content. Tiktokers present themselves as attractively as possible to attract the attention of the audience; this is done by Desy Genoveva, namely tiktokers with content using slang language on the account @desygenoveva_. The use of regional languages ​​has an impact on the use of communication styles and the meaning of the content presented. This research will discuss how the communication style conveyed in content uses slang language by tiktokers Desy Genoveva on the TikTok social media account @desygenoveva_. The method used is qualitative with content analysis of 16 ngapak language contents, starting with the mention "ngapak language...". The research results show that Desy Genoveva's communication style is a dominant style, dramatic style, animated style, impression style, and relaxed style. Based on this communication style, there are seven factors that influence communication style to produce a self-presentation strategy, namely managing appearance.